Pelatihan Penggunaan Google Classroom Sebagai Media Pembelajaran di SD Swasta PAB 15 - Fatmawati; Yusrizal; Syahrina Anisa Pulungan (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
as a learning medium in the pandemic era. The implementation of this activity is carried out online and offline. The online method is used by utilizing Google Meeting. While the offline method is implemented in order to evaluate the use of Google Classroom. The implementation of this activity lasted for three meetings with Google Classroom material, this training used the google meet application and training using learning videos. Participants in this activity consisted of elementary school teachers under the auspices of the North Sumatra PAB Foundation. Based on the results of the activity analysis, it can be concluded that after this activity there was an increase in teacher understanding in using and applying Google Classroom learning media. This increase can be seen from; 1) The teacher's ability to provide material through google classroom; 2) the ability of teachers to provide assessments using Google Classroom; and 3) the ability to make ice breaker through learning videos uploaded to Google Classroom.